POLA KERUANGAN PENYAKIT MENULAR (DBD) KOTA SEMARANG - Widjonarko Widjonarko; Iwan Rudiarto; Sri Rahayu (Department of Urban and Regional Planning, Diponegoro University, 2014)
The persistently high incidence of infectious diseases in the city of Semarang and spatial dynamics of its development shows an indication that the urban development in the city of Semarang not offset efforts to increase environmental health. Despite the high incidence of infectious diseases is still not matched by adequate research. Most of the research related to the spread of infectious disease is highlighted by the number and spatial spreading. These symptoms also started to affect the spatial spread of disease, where the villages with high incidence is likely to provide a positive influence on the spread of dengue disease in the surrounding villages.Based on the results of the research it is clear that the incidence of infectious diseases, particularly dengue fever leads to a pattern of endemic disease, where a high incidence of recurrence located in the same village in the time range 2006-2012.